A thematic dictionary of contemporary Chinese - Jiao, Liwei; Yang, Yan 1972-; Liu, Wei 1974 July 16- (Routledge, 2019)
"A Thematic Dictionary of Contemporary Chinese is a unique resource for intermediate to advanced students of Chinese. The dictionary presents 9,000 words organized thematically in 300 different subject areas. These themes cover the vocabulary necessary for daily use and for conducting meaningful conversations with native Chinese speakers on a variety of topics, from politics to business, and from hobbies to education. Each vocabulary item is annotated with the most frequent collocations allowing learners to improve their fluency by storing new vocabulary in larger linguistic units. Cultural and linguistic tips enable learners to grasp the vocabulary more effectively and increase their awareness of Chinese culture embedded in the language. Review exercises are provided throughout to ensure learners have ample opportunity to practice the new material. This is a great resource for both independent study and classroom use and will be of interest to students and teachers of Chinese alike. For further understanding of Chinese expressions, students are encouraged to read 500 Common Chinese Proverbs and Colloquial Expressions and 500 Common Chinese Idioms"--